Development of learning health system competency items related to health and healthcare equity and justice for rehabilitation researchers - Pamela M. Dunlap; Kathleen M. Poploski; Catherine A. Anderson; Thiru M. Annaswamy; Melissa A. Clark; Peter C. Coyle; Natalie F. Douglas; Ann Marie Flores; Janet K. Freburger; Brian J. Hafner; Kenneth J. Harwood; Jeanne M. Hoffman; et al. (Learning Health Systems)
Abstract Introduction In 2021, the Learning Health Systems Rehabilitation Research Network (LeaRRn) developed and administered a needs assessment survey, based on the Agency on Healthcare Research and Quality's (AHRQ's) original seven domains of learning health systems (LHS) researcher core competencies, to identify knowledge and interest in LHS research competencies among rehabilitation researchers. In 2022, the AHRQ added a new health and healthcare equity and justice (HE) domain to the existing seven domains for LHS researcher core competencies. Methods LeaRRn utilized methods similar to those employed in the development of their original needs assessment survey to generate and refine competency items for the HE domain. In this report, we describe the methods used to develop these HE competency items. Results & Conclusions Other training programs and LHS researchers may use the competency items developed for this needs assessment survey to identify training opportunities in the HE domain.